Role of alternative food and Allee in controlling chaos in an eco-epidemiological model with disease in the prey (Nonlinear Studies, 2022)
In this article, we have derived a prey-predator model assuming that the predator consumes both the susceptible as well as the infected prey following the modified Holling type-II functional response. The focuses of this study are the role of infection rate, alternative food, and allee in a predator-prey system including disease in the prey population. The existence and stability of the equilibrium points have been analysed. We have observed that the system enters into limit cycle oscillations from stable position, limit cycle to chaos for different parametric conditions. It is also shown that the infection rate, enrichment of the alternative food and allee can move the chaotic situation to limit cycle oscillations, limit cycle to a stable focus. This study provides insightful the ecological and the disease reproduction numbers for understanding how disease propagation in predator population in the presence of alternative food and Allee.